Adaptive framed pseudo-Bayesian Aloha algorithm with priorities - Habaebi, Mohamed Hadi; Mohd Ali, Borhanuddin (The Institution for Engineering and Technology (IET), 2000)
A new wireless framed pseudo-bayesian Aloha algorithm with adaptive priorities, for wireless ATM reservation-based TDMA MAC prolocols, is presented. The throughput in the presence of Rayleigh-fading, shadowing and capture is calculated, and the waiting time of the different priority classes is estimated using simulated models.